Real-World Experience of Vismodegib in Advanced Basal Cell Carcinoma at a Canadian Cancer Center. Issue 2 (March 2022) - Tong, Justin; Mitchell, Brandon; Roth, Kathryn; Logan, Diane; Ernst, Scott
Background: Vismodegib is a novel Hedgehog pathway inhibitor that has revolutionized the treatment of patients with advanced basal cell carcinoma (BCC) who are poor candidates for surgery or radiation. Few studies have explored the use of vismodegib to facilitate further surgery or radiotherapy, and the optimal treatment duration to balance outcomes with adverse effects. Objectives: To characterize the disease response, progression, and recurrence outcomes of BCC patients, and to report the impact of subsequent therapies. Methods: We performed a retrospective study of 46 adult patients with advanced basal cell carcinoma (aBCC), including both locally advanced (laBCC) and metastatic (mBCC) disease, treated with vismodegib at a single center from 2012 to 2019. Results: Thirty-six had laBCC, and 10 had mBCC. Treatment was given over a mean of 21.9 months. Twenty-three (50%) had a complete response (CR), and 19 (41.3%) achieved partial response (PR). Median time to maximal response was 5.3 months. Eleven (23.9%) had resected disease at median 17.2 months, and 11 patients (23.9%) received radiotherapy. Thirty-two (69.6%) experienced progressive disease after achievement of CR or PR. Among 17 CR patients, who stopped treatment, 14 (82.3%) experienced subsequent relapse; 6 (85%) attained a repeat response. Twenty (43.5%) discontinued treatment at least once due to adverse effects. Conclusions: With a response rate of 91%, London Regional Cancer Center's (LRCP)'s experience with vismodegib supports its effectiveness in treatment of aBCC. Moreover, a significant number of patients treated with vismodegib became amenable to surgery or radiotherapy. Toxicity remained an important factor that limited treatment duration.